Pengembangan Model Pembelajaran Reciprocal Teaching Pair Share (RTPS) Untuk Meningkatkan Kemampuan Metakognisi Matakuliah Mikrobologi Mahasiswa IKIP Budi Utomo - Lestari, Purwaning Budi; Widyaningrum, Diyah Ayu (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
One effort to improve college student metacognition through the development model of learning by constructivism approach the model of learning Reciprocal Teaching Pair Share (rtPS). RtPS learning model adopted from a blend of learning model Think Pair Share and Reciprocal teaching. The parameters for success by improving metacognition. The purpose of this research is to develop a learning model rtPS to improve student metacognition in microbiology course at the Teachers' Training College Budi Utomo. The research model of development used in this research is the development model 4D of Thiagarajan (1974). The 4D model has four stages, namely define, design, develop, and disseminate. Large-scale field trials using quasi-experimental. Testing the validity of data analysis techniques using Pearson correlation method according bivarian. Assessment of the effectiveness of product development conducted field trials involving three classes for large-scale testing. Testing differences in acquisition value aspects of metacognition capability in Teachers' Training College Budi Utomo Malang analyzed using General Linear Model (GLM) - Multivariate.The results showed that the development model of rtPS eligible for use in the learning activities. In large-scale trial can be concluded that the model rtPS ABILITY effect on students' metacognition. Besides the development of models rtPS effective in improving metacognitive abilities of students in the course of microbiology at the Teachers' Training College Budi Utomo Malang